Green Connected Automated Transportation and Safety Proceedings of the 11th International Conference on Green Intelligent Transportation Systems and Safety - Wang, Wuhong; Chen, Yanyan; He, Zhengbing; Jiang, Xiaobei; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
These proceedings gather selected papers from the 11th International Conference on Green Intelligent Transportation Systems and Safety, held in Beijing, China on October 17-19, 2020. The book features cutting-edge studies on Green Intelligent Mobility Systems, the guiding motto being to achieve "green, intelligent, and safe transportation systems". The contributions presented here can help promote the development of green mobility and intelligent transportation technologies to improve interconnectivity, resource sharing, flexibility and efficiency. Given its scope, the book will benefit researchers and engineers in the fields of Transportation Technology and Traffic Engineering, Automotive and Mechanical Engineering, Industrial and System Engineering, and Electrical Engineering alike. The readers will be able to find out the Advances in Green Intelligent Transportation System and Safety.
Advanced Driver Assistance Systems -- Car-2-X Communications -- Green and collaborative driving -- Energy and Emissions Solutions for Urban Traffic Operation -- HMI Design, including Driver Cognitive Behaviour, Driver Distraction -- Intelligent Highways and Traffic Modeling -- Electric Vehicles and Electricity Grids -- Electric Energy Storage System and In-transit Charging -- Vehicle-Infrastructure Automation -- Modeling and Simulation System for e-Mobility -- Big Data in E-Mobility -- Battery Technologies for Green Transportation -- Adaptive Mechanisms of Electricity grids and Charging System -- Energy and Emissions Solutions for Transit Operation -- Computer Vision for Intelligent Vehicle.
Keywords: Transportation engineering; Traffic engineering; Vehicles; Automotive engineering; Transportation Technology and Traffic Engineering; Vehicle Engineering; Automotive Engineering; Intelligent transportation systems -- Congresses; Green technology -- Congresses